2016
DOI: 10.1161/jaha.115.002484
|View full text |Cite
|
Sign up to set email alerts
|

Full Expression of Cardiomyopathy Is Partly Dependent on B‐Cells: A Pathway That Involves Cytokine Activation, Immunoglobulin Deposition, and Activation of Apoptosis

Abstract: BackgroundLimited information exists on the role of B‐cell‐dependent mechanisms in the progression of heart failure (HF). However, in failing human myocardium, there is evidence of deposition of activated complement components as well as anticardiac antibodies. We aimed to determine the contribution of B‐cells in HF progression using a nonsurgical mouse model of nonischemic cardiomyopathy (CMP).Methods and Results CMP protocol involved the use of l‐NAME and NaCl in the drinking water and angiotensin‐II infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 30 publications
3
77
0
3
Order By: Relevance
“…For instance, the pathogenesis of ANG II-induced dilated cardiomyopathy was reported to depend on the T cell Th2 phenotype (816) and to involve the Th2 polarizing cytokine IL-4 (815). Others recently showed that B cells have a contributory role in an ANG II-induced model of heart failure (186).…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 99%
“…For instance, the pathogenesis of ANG II-induced dilated cardiomyopathy was reported to depend on the T cell Th2 phenotype (816) and to involve the Th2 polarizing cytokine IL-4 (815). Others recently showed that B cells have a contributory role in an ANG II-induced model of heart failure (186).…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 99%
“…By contrast, M2-like macrophages (CD206 + F4/80 + CD11b + ) exert profound functions on tissue repair in heart depending on IL4 secretion (156). Recent studies implicate TNFβ producing B cells as a major contributor to myocardial fibrosis (153, 157). Antigen and cytokine stimulation are known to differentiate naive T cells into distinct T cell subpopulations that include T helper cells and CD4 + CD25 + FOXP3 + T Reg cells (158).…”
Section: Inflammation Innate and Adaptive Immune Responsesmentioning
confidence: 99%
“…Heart failure, hypertrophy, myocardial fibrosis, myocardial infarction, ischemia-reperfusion (43,44) TGF-β/smad signaling glg1, pdpk1(s117), jun(s63), lemd3, fbn2, men1, zeb1, aspn, eng, snx6, zfyve9, cav3, sptbn1, bcl9l, strap, cav2,* ppm1a, htra1…”
Section: Pathwaymentioning
confidence: 99%